La Cultura Organizacional en el Departamento de Jefatura del Uso de Espacio y Vía Pública del Gobierno Autónomo Descentralizado Municipal del Cantón Babahoyo - Minga Montece, Juleisi Michelle (2020)
The case study was carried out to describe the organizational culture practiced by the members of the Department of Headquarters for the Use of Space and Public Roads of the Municipal Autonomous Decentralized Government of the Babahoyo Canton, due to the fact that many inconveniences are provided in their work environment and in the Attention with its users, since through it it is intended to clear the doubt of knowing, whether a good organizational culture is exercised or not, likewise daily elements are shown about the working conditions in which the staff operates, considering that the Culture and the organizational climate are determining factors in administrative effectiveness. Taking into consideration that this department serves its clients directly, so it is essential that they have a good interpersonal relationship, so that their work performance and customer service are not affected.